Poly(Limonene Thioether) Scaffold for Tissue Engineering. Issue 7 (18th February 2016) - Fischer, Kristin M.; Morgan, Kathy Ye; Hearon, Keith; Sklaviadis, Demetra; Tochka, Zachary L.; Fenton, Owen S.; Anderson, Daniel G.; Langer, Robert; Freed, Lisa E.
Abstract : A photocurable thiol‐ene network polymer, poly(limonene thioether) (PLT32o), is synthesized, characterized, fabricated into tissue engineering scaffolds, and demonstrated in vitro and in vivo. Micromolded PLT32o grids exhibit compliant, elastomeric mechanical behavior similar to grids made of poly(glycerol sebacate) (PGS), an established biomaterial. Multilayered PL32o scaffolds with regular, geometrically defined pore architectures support heart cell seeding and culture in a manner similar to multilayered PGS scaffolds. Subcutaneous implantation of multilayered PLT32o scaffolds with cultured heart cells provides long‐term 3D structural support and retains the exogenous cells, whereas PGS scaffolds lose both their structural integrity and the exogenous cells over 31 d in vivo. PLT32o membrane implants retain their dry mass, whereas PGS implants lose 70 percent of their dry mass by day 31. Macrophages are initially recruited to PLT32o and PGS membrane implants but are no longer present by day 31. Facile synthesis and processing in combination with the capability to support heart cells in vitro and in vivo suggest that PLT32o can offer advantages for tissue engineering applications where prolonged in vivo maintenance of 3D structural integrity and elastomeric mechanical behavior are required. Abstract : A photocurable thiol‐ene network polymer is microfabricated into 3D pore architectures and demonstrated in vivo to provide long‐term structural support and exogenous heart cell retention. Facile synthesis, processing, and elastomeric mechanical properties in combination with the capability to support heart cells in vitro and in vivo suggest that this material can offer advantages in tissue engineering.